2020
DOI: 10.1002/jcla.23353
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression and diagnostic significance of P53, MutS homologs 2, tropomyosin‐4 in alpha‐fetoprotein‐negative hepatocellular carcinoma

Abstract: Background Current study aimed to explore the value of P53, MutS homologs 2 (MSH2), and tropomyosin‐4 (Tm‐4) combined with inflammatory factors, life‐history traits in the differential diagnosis of alpha‐fetoprotein‐negative hepatocellular carcinoma (AFP‐Negative HCC). Methods A testing cohort including 280 AFP‐Negative HCC patients and 300 controls was included. Three external validation cohorts from 3 centers were used to assess the novel logistic regression model inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
(63 reference statements)
0
3
0
Order By: Relevance
“…Liu et al concluded that des-gamma-carboxyprothrombin (DCP) can distinguish AFP-negative HBV-related HCC from chronic HBV infection (AUC = 0.731) or LC (AUC = 0.685) 48 . Several studies have attempted to combine multiple biomarkers [54][55][56][57][58][59][60][61] or serological examinations [62][63][64][65][66] . With the help of proteomics technology, researchers have identified some abnormally expressed proteins that were verified in various cancers [67][68][69][70] to construct a logistic regression model, which had good performance in distinguishing AFP-negative HCC 60 .…”
Section: Afp Is Used As a Biomarker In Hccmentioning
confidence: 99%
See 1 more Smart Citation
“…Liu et al concluded that des-gamma-carboxyprothrombin (DCP) can distinguish AFP-negative HBV-related HCC from chronic HBV infection (AUC = 0.731) or LC (AUC = 0.685) 48 . Several studies have attempted to combine multiple biomarkers [54][55][56][57][58][59][60][61] or serological examinations [62][63][64][65][66] . With the help of proteomics technology, researchers have identified some abnormally expressed proteins that were verified in various cancers [67][68][69][70] to construct a logistic regression model, which had good performance in distinguishing AFP-negative HCC 60 .…”
Section: Afp Is Used As a Biomarker In Hccmentioning
confidence: 99%
“…Several studies have attempted to combine multiple biomarkers [54][55][56][57][58][59][60][61] or serological examinations [62][63][64][65][66] . With the help of proteomics technology, researchers have identified some abnormally expressed proteins that were verified in various cancers [67][68][69][70] to construct a logistic regression model, which had good performance in distinguishing AFP-negative HCC 60 . A logistic regression model consisting of LHPP 71 -associated microRNAs (miR-363-5p and miR-765) and PIVKA-II exhibited a high identification value with an AUC of 0.930 57 .…”
Section: Afp Is Used As a Biomarker In Hccmentioning
confidence: 99%
“…59 Therefore, although, in the current study, the ORR and sORR yielded similar results, they probably measure different phenomena and, in clinical practice, might evaluate different populations. Also, from a molecular point of view, the subgroup of AFP-negative patients has been characterized 60 ; whereas, in those who have HCC with high AFP levels, several AFP-related activities could be hypothesized, such as immunosuppression, 41 regulation of tumor necrosis factor cytotoxicity, 61 and FAS-associated death-domain protein downregulation. 62 Therefore, serum AFP levels should correlate with the molecular characteristics.…”
Section: Discussionmentioning
confidence: 99%